2011
DOI: 10.1002/bjs.7675
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of liver ischaemia after pancreatic resection

Abstract: Postoperative liver perfusion failure is a rare but potentially severe complication following pancreatic surgery requiring immediate recognition and, if necessary, radiological or surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The ischemic complication in the liver rarely occurs after pancreatic resection, but it can cause a fatality when it happens. Hackert et al reported the influence of liver ischemia on clinical outcome after pancreatic resection [18]. Postoperative blood flow insufficiency in the liver caused sepsis and multiple organ failure in 5 of 17 patients (29.4%) who had ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…The ischemic complication in the liver rarely occurs after pancreatic resection, but it can cause a fatality when it happens. Hackert et al reported the influence of liver ischemia on clinical outcome after pancreatic resection [18]. Postoperative blood flow insufficiency in the liver caused sepsis and multiple organ failure in 5 of 17 patients (29.4%) who had ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing pancreatic resection without additional risk factors have a risk of liver ischemia of 2.2% [5]. Simultaneous involvement of the portal vein and hepatic artery was always fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Liver ischemia can occur in case of thrombotic occlusion of a reconstructed hepatic artery or celiac axis, respectively, and is characterized postoperatively by strongly increasing liver enzymes as well as a vascular flow decrease in ultrasound or CT examination. Especially when a synchronous venous resection and reconstruction has been performed, this complication may be aggravated by venous thrombosis leading to fatal liver ischemia and requiring an immediate surgical or interventional management to restore adequate arterial (and portovenous) inflow (17).…”
Section: Surgical Considerations Of Arterial Resection and Replacementmentioning
confidence: 99%